(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2005)
Using the algebraic structure of cyclic codes an efficient method for the determination of the weight distribution of the cosets of cyclic codes is presented. As an illustration of the method weight distributions of the coset leaders of all ternary cyclic codes of lengths up to 14 are calculated.